Did the Intergenerational Solidarity Pact increase the employment rate of older workers in Belgium? A macro-econometric evaluation - Muriel Dejemeppe; Catherine Smith; Bruno Van der Linden (IZA Journal of Labor Policy, 2015)
In December 2005, the Belgian government adopted the law on the Intergenerational Solidarity Pact (ISP) aimed at increasing the employment rate of older workers. The main policies of the ISP consist of a pension bonus, reductions in employers' social security contributions and measures discouraging early retirement while encouraging working time reductions at the end of the career. We aim at evaluating the overall effectiveness of the ISP in raising the employment rate of older workers. To that purpose, we compare the actual evolution of the employment rate after the implementation of the policies to its predicted (counterfactual) evolution based on the estimation of a macro-econometric model in a period prior to the ISP. The results suggest a slight positive impact of the ISP on the employment rate of older workers but to the detriment of the younger workers. However, there is a lack of statistical power to draw firm conclusions on the overall effect of the ISP.
Keywords: J21; J26; H53; E32; 330; Aging; Evaluation of labor market policies; Macro-econometrics